QUALITY CONTROL MANAGEMENT SYSTEM DESIGN: FRAMEWORK-BASED OF SIPRIMA MOBILE APPLICATION - Yans Fithratul I.; Erlangga Lesmana Putra; Fitri Dwi Fadilah; Megawati Putri Martinez; Kevin Igor Ibnu Listanto; Mochammad Rifki Ulil Albaab (International Journal of Computer Science and Information Technology, 2024)
Nowadays, technological developments have a profound impact on all areas of human life. We as humans cannot avoid the influence of the evolution of the times, as well as with the business world. The use of technology in the world of business has a tremendous positive influence, so PT Prima Teknikindo Raya created an application called SiPrima. The Siprima application is an application that serves as a recording and management system for PT Prima Tekindo Raya. This application was created to solve the problems that are owned by PT Prima Technikindo Raya, which is the recording system that is still manual and is considered quite difficult, therefore it was created an app called SiPrimima which can help solve problems experienced by the PT Prima Techindo Raya based on Android to make it easier to work [1] to be able to avoid the influence of the development of the times, as well as with the business world. The use of technology in the world of business has an extraordinary positive influence, so the company PT.Prima TeknikIndo Raya created an application called “SiPrima”. The application SiPrima is an application that functions as a quality control management system of production quality of products within the company. The application was developed to address the issue of the management of the quality control system's ineffectiveness and efficiency in controlling production quality. Therefore, it was created a Siprima application that can help solve problems experienced by the Company